2000
DOI: 10.1128/jvi.74.2.593-599.2000
|View full text |Cite
|
Sign up to set email alerts
|

The VP5 Domain of VP4 Can Mediate Attachment of Rotaviruses to Cells

Abstract: Some animal rotaviruses require the presence of sialic acid (SA) on the cell surface to infect the cell. We have isolated variants of rhesus rotavirus (RRV) whose infectivity no longer depends on SA. Both the SA-dependent and -independent interactions of these viruses with the cell are mediated by the virus spike protein VP4, which is cleaved by trypsin into two domains, VP5 and VP8. In this work we have compared the binding characteristics of wild-type RRV and its variant nar3 to MA104 cells. In a direct nonr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
67
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 35 publications
0
67
0
3
Order By: Relevance
“…The RRV VP5 fragment (VP4 gene nucleotides 749 to 2347) was cloned in pGEX-4T-2 (Pharmacia) as previously described (Zarate et al, 2000b). Expression and purification of fusion proteins was performed following previously described standard procedures (Frangioni and Neel, 1993).…”
Section: Generation Of Fusion Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RRV VP5 fragment (VP4 gene nucleotides 749 to 2347) was cloned in pGEX-4T-2 (Pharmacia) as previously described (Zarate et al, 2000b). Expression and purification of fusion proteins was performed following previously described standard procedures (Frangioni and Neel, 1993).…”
Section: Generation Of Fusion Proteinsmentioning
confidence: 99%
“…SA-dependent rhesus rotaviruses (RRV) initially bind to the cell through VP8 (Fiore et al, 1991;Isa et al, 1997), whereas variants of RRV that no longer depend on the presence of SA (e.g. nar3), interact with the cell through VP5 (Zarate et al, 2000b).…”
mentioning
confidence: 99%
“…Two surface proteins, VP4 and VP7, are present on the outer capsid of rotaviruses, and trypsin cleavage of the spike protein VP4 into VP5* and VP8* enhances rotavirus infectivity and is involved in the early interaction of the virus with the cell (18,67). Rotaviruses infect the mature enterocytes of the villus epithelium of the small intestine.…”
mentioning
confidence: 99%
“…It has been reported that recombinant VP8 protein, produced in bacteria as a fusion product with glutathione Stransferase (GST-VP8), was found to bind to MA104 cells in a specific and saturable manner and that it was capable of inhibiting the binding of a homologous virus when it was preincubated with MA104 cells [24]. To confirm the specificity of binding of an avian rotavirus to sialic acid on the cell surface, we prepared GST-VP8 of strain PO-13 and carried out a binding assay using purified GST-VP8.…”
mentioning
confidence: 99%
“…There is evidence that rotaviruses have multiple plasma membrane receptors, including sialic acid (SA) [6], integrins [4] or other membrane proteins [13]. Some animal rotaviruses can bind to the cell either through interactions mediated by VP8 or VP5 via SA-containing and SA-independent cell surface receptors, respectively [7,24]. Human strains appear to use an SA-independent route [6], and an α2β1 integrin-binding motif (DGE) present in VP5 at amino acids 308-310 may function as the receptor-binding site [23].…”
mentioning
confidence: 99%